2013
DOI: 10.1002/mnfr.201300067
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ovalbumin glycoconjugates on alleviation of orally induced egg allergy in mice via dendritic‐cell maturation and T‐cell activation

Abstract: This study validates, for the first time, the use of OVA-glycated mannose and glucomannan for potential beneficial dietary interventions for allergy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 38 publications
2
56
1
Order By: Relevance
“…Glycation of allergens via Maillard reaction or chemical conjugation influences the susceptibility to food-induced allergies. The ovalbumin-mannose treated mice have less histamine and more Tregs than the control mice [75] . These studies support the hypothesis that histamine levels are inversely correlated with the activity of Tregs.…”
Section: Histamine and Regulatory T Cells In Allergic Dermatitis (Figmentioning
confidence: 88%
“…Glycation of allergens via Maillard reaction or chemical conjugation influences the susceptibility to food-induced allergies. The ovalbumin-mannose treated mice have less histamine and more Tregs than the control mice [75] . These studies support the hypothesis that histamine levels are inversely correlated with the activity of Tregs.…”
Section: Histamine and Regulatory T Cells In Allergic Dermatitis (Figmentioning
confidence: 88%
“…Analysis of the correlation between glycosylation and allergenicity variation indicated an uncertain effect of either increased or decreased allergenicity induced by Maillard reaction during food processing [ 20 ]. Nevertheless, reducing the allergenicity of food allergens using glycosylation or the Maillard reaction is a promising strategy that has been studied in related research to determine the correlation between the secondary structure of proteins and the resulting allergic reactions [ 21 ]. Furthermore, the loosing of conformational structure during the process of Maillard reaction would increase the possibility to form polymerization and aggregation [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…44 Administration of Man 51 -BSA decreased the anaphylactic response by targeting a C type lectin receptor, SIGNR-1, which conditions dendritic cells in the lamina propria and favored generation of CD4C type 1 regulatory like cells expressing IL-10 and IFN-g. Another study employed a similar approach and evaluated glycated forms of ovalbumin. 45 They found that treatment with these modified antigens decreased specific IgE and clinical signs after oral challenge. They also found a decrease in maturation and uptake by DCs and an increase in the percentage of T regulatory cells.…”
Section: Modified Food Allergensmentioning
confidence: 99%